2020
DOI: 10.1371/journal.pone.0232027
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and practices of exclusive breastfeeding among mothers in rural areas of Rajshahi district in Bangladesh: A community clinic based study

Abstract: Background World Health Organization (WHO) suggests that exclusive breastfeeding (EBF) is the best nutrition for the neonate. Still, it remains a big challenge to establish EBF not only in Bangladesh but also in any developing countries. Objective The aim of this study was to determine the level of knowledge and practices on EBF and its relationship between different socioeconomic and demographic factors among mothers having at least one child of aged 6-12 months in the rural area of Rajshahi District, Banglad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 35 publications
(42 reference statements)
4
16
2
Order By: Relevance
“…This study demonstrated that about two-thirds of mothers (63.4%) exclusive breastfed their child up to 6 months of age, which is close to the national level (65%) in Bangladesh 13 . The prevalence of EBF in this study was higher than other studies conducted in Bangladesh such as a study conducted among Bangladeshi mothers in a rural area which reported a prevalence of EBF of 35.9% 15 and another study conducted in the rural area of Rajshahi district which reported an EBF practice rate of 34.5% 16 . In both studies, the rural areas lacked health facilities and a large proportion of participants was illiterate.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…This study demonstrated that about two-thirds of mothers (63.4%) exclusive breastfed their child up to 6 months of age, which is close to the national level (65%) in Bangladesh 13 . The prevalence of EBF in this study was higher than other studies conducted in Bangladesh such as a study conducted among Bangladeshi mothers in a rural area which reported a prevalence of EBF of 35.9% 15 and another study conducted in the rural area of Rajshahi district which reported an EBF practice rate of 34.5% 16 . In both studies, the rural areas lacked health facilities and a large proportion of participants was illiterate.…”
Section: Discussioncontrasting
confidence: 82%
“…In contrast, this study found that some sociodemographic factors such as being a housewife, literate, having a high income, and being a single family, were more likely to practice EBF. Previous studies conducted among Malaysian 20 and Indian mothers 21 reported that non-working/housewife mothers were more likely to have good EBF practices than employed mothers who had poor knowledge and attitude toward EBF practice, leading to less exclusive breastfeeding practices, as found among Nepali 22 and Bangladeshi 16 mothers. Housewives can easily participate in Government and NGO implemented programs on Infant and Young Feeding (IYCF) practices available in the community, which makes them more positive toward EBF practices.…”
Section: Discussionmentioning
confidence: 84%
“…Higher maternal education increases women’s opportunities for employment, household earnings, and autonomy; empowers the woman to make informed child health-related decisions such as the uptake of appropriate IYCF information; and improves the woman’s attitude towards seeking appropriate child health support for appropriate IYCF [ 82 ]. While some studies have shown that women in employment have advantages of improving earnings/confidence and subsequent health-related decisions for IYCF [ 67 , 86 , 87 , 88 ], other studies have indicated that “stay-at-home” mothers (housewives) also have advantages for appropriate IYCF [ 89 , 90 ]. Being a housewife allows the mother to have enough time and support for careful consideration of appropriate IYCF practices, and the mother is not distracted by external work activities compared to the mother in employment [ 89 , 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…Repatriation of thousands of Bangladeshi people firstly from China in January and then from all other COVID-19 affected countries, and the mismanagement of their screening, quarantine, and isolation created a huge debate both in media and the public [ 14 ]. All our respondents were educated and most of them came from urban settings.…”
Section: Discussionmentioning
confidence: 99%
“…Since our target population is known (25, 95,197), the following formula was used for determining the sample size: n = N/ (1+Nd 2 ), where n = required sample size, N = population size (25, 95,197), d = marginal error (0.05) [ 12 , 13 ]. The formula provided that the minimum sample size of 400 would be sufficient for this study.…”
Section: Methodsmentioning
confidence: 99%